2023
DOI: 10.1002/ijgo.14757
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve in patients with multiple sclerosis: A systematic review and meta‐analysis

Abstract: ObjectiveTo summarize recent evidence about ovarian reserve markers in women affected by multiple sclerosis (MS) compared with healthy controls, as women with MS seem to be characterized by lower anti‐Müllerian hormone (AMH) levels.MethodsThe research was conducted using PubMed (MEDLINE), Scopus, ClinicalTrial.gov, OVID and Cochrane Library from inception of each database to June 30, 2022. Studies comparing ovarian reserve markers between women with MS and healthy controls were considered eligible for inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In our study, AMH levels diminished with participants' age as expected. There was no significant difference between MS patients and controls, consistent with recently published data, supporting the notion that MS does not impact fertility ( 25 ). However, we found a tendency of having lower values in young MS patients.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, AMH levels diminished with participants' age as expected. There was no significant difference between MS patients and controls, consistent with recently published data, supporting the notion that MS does not impact fertility ( 25 ). However, we found a tendency of having lower values in young MS patients.…”
Section: Discussionsupporting
confidence: 90%
“…However, recent larger studies and a systematic review and meta-analysis on ovarian reserve in patients with multiple sclerosis suggested no significant difference in serum AMH or follicle-stimulating hormone levels, nor the ovarian volume [36 ▪ ,37]. Antral follicle count (AFC) and estradiol blood levels were significantly lower, and luteinizing hormone (LH) levels were significantly higher in in WwMS, than in controls [36 ▪ ]. A large claims-based study suggested that a greater proportion of women with MS than without had a diagnosis of infertility and despite this, fewer women with MS than without used any infertility treatment.…”
Section: Pre-conceptionmentioning
confidence: 98%
“…Higher incidence of thyroid autoimmunity, higher grade endometriosis, and primary and secondary sexual dysfunction, fatigue, and other MS-related symptoms have been invoked as culprits for this observation [33–35]. There have been conflicting publications about ovarian function and markers of ovarian reserve in WwMS [36 ▪ ]. Anti-Mullerian hormone (AMH) was thought be decreased in women with MS versus healthy women, and in women with more active disease course [33].…”
Section: Pre-conceptionmentioning
confidence: 99%
See 1 more Smart Citation